2016
DOI: 10.1038/srep32467
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Microbiome of a Halophyte and its Role in Helping Non-Host Plants to Withstand Salinity

Abstract: Root microbiota is a crucial determinant of plant productivity and stress tolerance. Here, we hypothesize that the superior halo-tolerance of seepweed Suaeda salsa is tightly linked to a specialized belowground microbiome. To test this hypothesis, we performed a phylogenetic trait-based framework analysis based on bacterial 16S rRNA gene and fungal nuclear rRNA internal transcribed spacer profiling. Data showed that the dominant α-proteobacteria and γ-proteobacteria communities in bulk soil and root endosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 80 publications
4
117
1
1
Order By: Relevance
“…brachiata and showed that the halobacteria were involved in indole acetic acid production, phosphate solubilization, and 1‐aminocyclopropane‐1‐carboxylic acid deaminase activity. In a recent study, Yuan et al () demonstrated that the microbiome of Suaeda salsa could help to improve nonhost plants growth and salt tolerance.…”
Section: Halophyte Cultivation and Its Potential Applicationsmentioning
confidence: 99%
“…brachiata and showed that the halobacteria were involved in indole acetic acid production, phosphate solubilization, and 1‐aminocyclopropane‐1‐carboxylic acid deaminase activity. In a recent study, Yuan et al () demonstrated that the microbiome of Suaeda salsa could help to improve nonhost plants growth and salt tolerance.…”
Section: Halophyte Cultivation and Its Potential Applicationsmentioning
confidence: 99%
“…The area of BNF research has been expanded by the discovery of N-fixing bacterial endophytes in non-nodulating plants. Bacterial endophytes promote plant growth through nitrogen fixation, phytohormone production, nutrient acquisition and by conferring tolerance to abiotic and biotic stresses (Haney et al, 2015;Berg et al, 2016;Yuan et al, 2016;Santoyo et al, 2017). They most often inhabit the plant intercellular spaces, which are abundant in carbohydrates, amino acids and inorganic nutrients (Compant et al, 2011;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shi et al (2015) analyze the changes in microbial rhizosphere communities of the annual grass Avena fatua in two growing sessions and found that in spite of the different starting communities in both seasons, the successional patterns were similar and the final communities were very similar. On the other hand, Yuan et al (2016) analyzed the rhizosphere of the seepweed Suaeda salsa and found that both phylogenetic clustering (abiotic factors) and overdispersion (biotic factors) are involved in the high tolerance to salinity in this plant species. The genus Tagetes has been characterized as exuding allelopathic compounds of the thiophenes type which have a nematocide function that has been demonstrated in both field and laboratory (Riga et al, 2005).…”
Section: Discussionmentioning
confidence: 99%